Modification of high-speed steel phase composition and microhardness by combined plasma and thermal treatment - Cherenda, Nikolai N.; Uglov, Vladimir V.; Kashevski, Alexander M.; Astashynski, Valentin M.; Kuzmitski, Anton M. (Journal of the Belarusian State University. Physics, 2019)
Phase and element composition, microhardness of the NbC - high-speed steel system subjected to the combined effect of compression plasma flows impact and heat treatment were investigated in this work. X-ray diffraction analysis, scanning electron microscopy, energy dispersion microanalysis and microhardness measurements were used for investigation of the modified layer structure and properties. The findings showed that the plasma impact on the NbC - high-speed steel system led to carbides dissolution and ε-NbN and β-Nb2N nitrides formation. Growth of the energy absorbed by the surface resulted in niobium concentration decrease in the analyzed layer. Dissolution of carbides was the reason of microhardness diminishing. Subsequent annealing in air during 9 h at the temperature 600 C led to microhardness increase by a factor of 1.3 compared with the initial steel sample.